Why Freud was wrong : sin, science, and psychoanalysis - Webster, Richard, 1950- (New York, NY : BasicBooks, 1995)
The importance of Sigmund Freud to the history of the twentieth century needs no demonstration. Yet, as criticism of Freud has mounted, all the major biographies of this central figure in our culture have been written either by admirers or by authors who are themselves psychoanalysts. Why Freud Was Wrong sets out to redress the imbalance and to offer a definitive answer to controversies that have raged with increasing bitterness in recent years. It is the first complete and coherent account of Freud's life and work to be written from a consistently skeptical point of view. It is also an unusual and successful exercise in intellectual archaelogy.
In a new analysis of the origins of psychoanalysis, Richard Webster traces Freud's essentially religious personality to his childhood and shows how the founder of psychoanalysis, burdened by his parents' reverence and expectations, allowed his messianic dreams to shape the "science" he created. He examines the manner in which Freud - far from being the fearless and independent thinker of psychoanalytic legend - repeatedly fell under the spell of charismatic theorists who were mistaken or deluded. Having shown how Freud again and again misdiagnosed his patients and failed to work the cures he claimed, Webster goes on to question his most important theoretical formulations. Through a careful analysis of cultural history, he shows that Freud's sexual theories were in reality religious doctrines in disguise, safe from the attacks of science precisely because they were presented as science.
Includes bibliographical references (p. 553-646) and index.
Keywords: Freud, Sigmund, -- 1856-1939.; Psychoanalysis -- History